Cambio técnico, ciclo laboral y productividad del trabajo en una empresa cafetalera costarricense, 1946-1961 - Rojas Bolaños, Margarita (1994)
Information from weekly payrolls of the González Flores coffee firm, for the years 1946 and 1961, is applied to a study of labor cycles and systems on several coffee plantations belonging to the firm. Together with other data form the company archives, form informants and form secondary sources, certain initial conclusions are reached regarding attempts to intensify production by means of additional fertilizers and labor.